(untitled) (European Journal of Emerging Technology and Discoveries, 2024)
This article presents the results of research work carried out at the Uzbek Research Institute of Natural Fibers in close cooperation with the Fergana Polytechnic Institute to improve the technology of preparing raw silk for the production of a new range of fine, elegant and spectacular silk fabrics. The purpose of this research was to create a new range of fine, spectacular silk fabrics from natural silk by improving the technology of preparing raw silk threads for weaving. The new range of fine, spectacular silk dress fabrics is produced from raw silk with a linear density of 2.33 tex. In this case, both the warp and weft threads from raw silk are imparted a certain twist in the S direction on the TKM-8-12 dovetailing and twisting machine. The article also presents the results of laboratory tests of both raw silk and twisted threads in the testing laboratory of the institute. Based on the results of the conducted research, appropriate conclusions were made and recommendations for their use were given.